2022
DOI: 10.1177/0976500x221147798
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TLR-4 Signaling to Treat COVID-19-induced Acute Kidney Injury

Abstract: The newly discovered severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) has turned into a potentially fatal pandemic illness. Numerous acute kidney injury (AKI) cases have been reported, although diffuse alveolar destruction and acute respiratory failure are the major symptoms of SARS-CoV-2 infection. The AKI, often known as a sudden loss of kidney function, carries a greater risk of mortality and morbidity. AKI was the second most frequent cause of death after acute respiratory distress syndrome (ARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…Recent evidence has suggested that the binding of TLR4 to the SARS-CoV-2 spike protein could serve as an alternative gateway into human cells, ultimately, aggravating the hyperinflammatory response characterized by increased TNF- α , interleukin (IL)-1, IL-2, IL-6, IL-7, IL-18, interferon-gamma, granulocyte-macrophages colony-stimulating factor, and monocyte chemoattractant protein-levels, known as a cytokine storm, a hallmark feature of COVID-19 ( Fig. 1 ) [ 62 ]. In that regard, it has been documented that TLR4 has a stronger protein–protein interaction with SARS-CoV-2 compared to ACE2, with binding energy values of –120.2 and –29.2, respectively (the more negative, the stronger the binding) [ 63 ], a critical observation that requires further investigation.…”
Section: Potential Role Of Tlr-4 In Covid-19mentioning
confidence: 99%
“…Recent evidence has suggested that the binding of TLR4 to the SARS-CoV-2 spike protein could serve as an alternative gateway into human cells, ultimately, aggravating the hyperinflammatory response characterized by increased TNF- α , interleukin (IL)-1, IL-2, IL-6, IL-7, IL-18, interferon-gamma, granulocyte-macrophages colony-stimulating factor, and monocyte chemoattractant protein-levels, known as a cytokine storm, a hallmark feature of COVID-19 ( Fig. 1 ) [ 62 ]. In that regard, it has been documented that TLR4 has a stronger protein–protein interaction with SARS-CoV-2 compared to ACE2, with binding energy values of –120.2 and –29.2, respectively (the more negative, the stronger the binding) [ 63 ], a critical observation that requires further investigation.…”
Section: Potential Role Of Tlr-4 In Covid-19mentioning
confidence: 99%